2009
DOI: 10.1249/mss.0b013e3181864bee
|View full text |Cite
|
Sign up to set email alerts
|

Does Padded Headgear Prevent Head Injury in Rugby Union Football?

Abstract: Padded headgear does not reduce the rate of head injury or concussion. The low compliance rates are a limitation. Although individuals may choose to wear padded headgear, the routine or mandatory use of protective headgear cannot be recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
119
0

Year Published

2010
2010
2014
2014

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 101 publications
(123 citation statements)
references
References 31 publications
3
119
0
Order By: Relevance
“…13,[19][20][21][22][23][24][25][26][27][28][29][30][31][32] In 2 cases, 13,27 supplementary articles 33,34 were accessed in order to extract the full details of the study methods. The QUORUM statement flow diagram, summarizing the process of study selection and the number of studies excluded at each stage, with explanations, is shown in the Figure. The main reasons for exclusion were nonprospective study design (n = 16), adult population (n = 3), and insufficient data on the adolescent cohort in cases of mixed adolescent and adult populations (n = 6).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…13,[19][20][21][22][23][24][25][26][27][28][29][30][31][32] In 2 cases, 13,27 supplementary articles 33,34 were accessed in order to extract the full details of the study methods. The QUORUM statement flow diagram, summarizing the process of study selection and the number of studies excluded at each stage, with explanations, is shown in the Figure. The main reasons for exclusion were nonprospective study design (n = 16), adult population (n = 3), and insufficient data on the adolescent cohort in cases of mixed adolescent and adult populations (n = 6).…”
Section: Resultsmentioning
confidence: 99%
“…27,28 All had at least 1-season follow-up, and 6 groups [20][21][22]25,26,30 investigated only a single team. Participant dropout was clearly accounted for in just 3 studies, 13,23,27 and ethical approval was confirmed in only 7.…”
Section: Methodologic Designmentioning
confidence: 99%
See 3 more Smart Citations